A case report of anti-NMDA receptor encephalitis in a young Egyptian female patient presenting with hyperreligiosity - Hamdi Ibrahim; Attaa Ali; Safwat Abdel Maksod; Magdy Khorshed; Mona Wassef; Mostafa Alfishawy; Hanan Rady; Adel Mohamed; Mohamed Mahmod; Khaled Ismael; Marwa Haron; Suzan Said; et al. (SpringerOpen, 2023)
Abstract Anti-n-methyl-d-aspartate receptor (NMDAR) encephalitis is a form of autoimmune encephalitis that remains under-recognized due to the variability of the initial symptoms and can be misdiagnosed as viral encephalitis or other pathogens. This syndrome has been predominantly described in young females including personality changes, autonomic dysfunctions, and neurologic decompensation. About half of the cases have tumors, most commonly teratomas of the ovaries; another established trigger is herpes viral encephalitis, while the cause in other cases is unclear. In case of clinical suspicion, electroencephalogram and brain magnetic resonance imaging are useful, but lumbar puncture for cerebrospinal fluid analysis is used to confirm the diagnosis. Treatment for this disease includes immunosuppression, plasmapheresis, and tumor resection when indicated. In this case report, we present a case that presented with hyperreligiosity and proved to have autoimmune encephalitis. The main purpose of our case is to increase awareness regarding immune-mediated encephalitis, especially the anti-NMDAR encephalitis.